Cardiorespiratory fitness and long‐term risk of sleep apnea: A national cohort study. (7th April 2019) - Crump, Casey; Sundquist, Jan; Winkleby, Marilyn A.; Sundquist, Kristina
Summary: Sleep apnea is increasing in prevalence, and is an important cause of cardiometabolic diseases and mortality worldwide. Its only established modifiable risk factor is obesity; however, up to half of all sleep apnea cases may occur in non‐obese persons, and hence there is a pressing need to identify other modifiable risk factors to facilitate more effective prevention. We sought to examine, for the first time, cardiorespiratory fitness in relation to the risk of sleep apnea, independent of obesity. A national cohort study was conducted to examine cardiorespiratory fitness in all 1, 547, 478 Swedish military conscripts during 1969–1997 (97%–98% of all 18‐year‐old men) in relation to risk of sleep apnea through 2012 (maximum age 62 years). Cardiorespiratory fitness was measured as maximal aerobic workload in Watts, and sleep apnea was identified from nationwide outpatient and inpatient diagnoses. A total of 44, 612 (2.9%) men were diagnosed with sleep apnea in 43.7 million person‐years of follow‐up. Adjusting for age, height, weight, socioeconomic factors and family history of sleep apnea, low cardiorespiratory fitness at age 18 years was associated with a significantly increased risk of sleep apnea in adulthood (lowest versus highest cardiorespiratory fitness tertile: incidence rate ratio, 1.44; 95% confidence interval, 1.40–1.49; p < 0.001; continuous cardiorespiratory fitness per 100 Watts: incidence rate ratio, 0.71; 95% confidence interval, 0.70–0.73; p < 0.001). An increased risk was observed even among men with normal body mass index (lowest versus highest cardiorespiratory fitness tertile: incidence rate ratio, 1.30; 95% confidence interval, 1.26–1.35; p < 0.001). These findings identify low cardiorespiratory fitness early in life as a new modifiable risk factor for development of sleep apnea in adulthood.